Social media use, depression and quality of life: a brief review - Ahmad Othman, Akmarina (Human Resources Management Academic Research Society, 2024)
The internet use has been increasing from 87.4% in 2018 to 92.7% in 2022 and a large number of internet users in Malaysia utilize it for social networking purposes. The Covid-19 pandemic also plays a role in this increment. The use of excessive social media use has shown to affect social and occupational functioning, as well as psychological health. However, a positive association between social media use with positive mental health has been reported as well. Previous studies on the matters have been emphasizing on students rather than adults population in general. Nevertheless, given the large prevalence of depression in adults over the age of 18, and the fact that it is far more common among unemployed compared to students, it is essential that future research to focus on the adult population rather than just students. Therefore, this paper shows a brief review on the social media use with depression and quality of life, looking at the positive and negative sides of social media use. In addition, this paper also lays out the recommendations for the future study.